Unleashing the power of ChatGPT in finance research: opportunities and challenges - Zifeng Feng; Gangqing Hu; Bingxin Li; Jinge Wang (Financial Innovation)
Abstract Natural language processing (NLP) technologies, such as ChatGPT, are revolutionizing various fields, including finance research. This article explores the potential of ChatGPT as a transformative tool for finance researchers. We illustrate various applications of ChatGPT in finance research, from analyzing financial charts and providing coding support to the theoretical derivation of financial models. Significant advances in multimodal learning, such as Visual Referring Prompting (VRP), are also explored for their potential to enhance ChatGPT's image analysis capabilities. Furthermore, we conduct a comparative analysis of ChatGPT-3.5, ChatGPT-4, and Microsoft Bing to examine their distinct features, strengths, and weaknesses to provide valuable insights into their applicability in finance research. We demonstrate the innovative opportunities and insights provided by the development of ChatGPT to enrich the financial research process. By addressing the potential pitfalls and ethical considerations associated with using ChatGPT, we aim to promote responsible AI adoption and a more in-depth understanding of the role of advanced NLP technologies in shaping the future of finance research and practice. Overall, this paper underscores ChatGPT's transformative role in finance research, detailing its applications, benefits, and challenges, and advocating for ethical AI adoption to shape the future of the field.